The relationship between mitotic rate and depth of invasion in biopsies of malignant melanoma - Ghasemi Basir HR; Alirezaei P; Ahovan S; Moradi A (Dove Medical Press, 2018)
Hamid Reza Ghasemi Basir,1,2 Pedram Alirezaei,2 Sara Ahovan,3 Abbas Moradi3 1Department of Pathology, School of Medicine, Hamadan University of Medical Sciences, Hamadan, Iran; 2Psoriasis Research Center, Hamadan University of Medical Sciences, Hamadan, Iran; 3School of Medicine, Hamadan University of Medical Sciences, Hamadan, Iran Background: Malignant melanoma of the skin is a potentially lethal neoplasm that generally originates from atypical melanocytes in the dermal–epidermal junction. When the neoplasm penetrates into the dermis, several variables can affect the extent of its spread, among which depth of invasion has the most important prognostic value. Mitotic rate is another prognostic factor that reflects the biological behavior of the neoplasm.Objective: This study was designed to evaluate the probable relationship between the depth of invasion of malignant melanoma and its mitotic rate.Materials and methods: This study was performed on 50 excisional biopsy specimens that had received the diagnosis of malignant melanoma histopathologically. Tumor characteristics including Breslow thickness, Clark level, T-stage, and tumor mitotic rate were recorded.Results: We observed that at higher Clark levels and higher T-stages, and the mean mitotic rate was significantly increased. Moreover, there was a positive and significant correlation between Breslow thickness and mitotic rate. We demonstrated that one unit increase in mitotic rate was correlated with 0.8 mm increase in Breslow thickness of the tumor.Conclusion: In malignant melanoma, mitotic activity may probably indicate the depth of tumor invasion. Therefore, in incisional biopsies where depth of invasion cannot be accurately determined, the mitotic activity may be used to estimate Breslow thickness, which is necessary for planning surgical management. Keywords: melanoma, mitosis, Breslow, invasion, thickness, proliferation